PENGARUH KOMPETENSI, MOTIVASI, DISIPLIN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAH RAGA KABUPATEN TOJO UNA-UNA - Sudirman, Sudirman (Katalogis, 2017)
The aim of this study is to determine and analyze simultaneous and partial influence of competency, motivation, disciplin, and work satisfaction on officials’ performance in The Department of Education, Youth, and Sport, Tojo Una-Una. Respondents comprise of 44 officials defined through Slovin formula with random proportional sampling method. Analysis tool used is multiple linear regressions. The study underlines that competency, motivation, disciplin, and work satisfaction simultaneously and partially influence officials performance in The Department of Education, Youth, and Sport, Tojo Una-Una.